COMIC STRIPS IN ELT: REVISITING “THE WHEN AND HOW” - Nine Febrie Novitasari (English Education Department, 2020)
Few know that comic strips can be used in educational contexts, particularly in English language classrooms. If associated with the purpose of language teaching, the use of comic strips is to facilitate students to develop their three learning domains: cognitive, affective, and psychomotor domains. Integrating comic strips in classroom activities will make the process of learning more meaningful. In Indonesian context, the teaching and learning process utilising comics is still rare to find. Most Indonesian EFL teachers usually only focus on enhancing students’ reading comprehension skill when using comic strips in their teaching. They ignore other objectives such as providing the students’ other language skills, introducing the culture embedded, or sharping students’ learning domains. Such a problem occurs because the teachers do not know and are not sure of how to find good and suitable comics for their students. In addition to that, many teachers admit that it is quite difficult to prove and to convince the parents that comics can be used as stimulating, pedagogically-suitable learning media. Concerning the issue, this paper presents a comprehensive explanation on the nature of comic that suits the purpose of EFL/ESL teaching and and offers some best practices for English teachers to utilize comic strips in their teaching. It is expected that after reading this paper, EFL teachers in Indonesia can explore their belief and practice in implementing comics and bring up a new trend in EFL classroom.